(untitled) - Tukur, Nuhu Ibrahim

Effect of biological oxidants on the functioning of MEP pathway’s [Fe-S] cluster-dependent enzymes (Stellenbosch : Stellenbosch University, 2023)
Tukur, Nuhu Ibrahim. 2023. Effect of biological oxidants on the functioning of MEP pathway’s [Fe-S] cluster-dependent enzymes. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/ce673701-e16c-416e-9dde-722184fe8b85